The concept of Tazkiyah Al-Nafs in the female character in the novel the missing piece. - Zainal Abidin, Nur Lailatul Akma; Kamarudin, Kamariah (2011)
This study aims to analyse the elements of tazkiyah al-nafs (purification of the soul) in the novel The Missing Piece: Part One and Part Two. In general, character studies discuss three important aspects, one of which is the spiritual. In this study, the researcher will lay emphasis on the message of spirituality depicted by the author through the female character in the novel. This spiritual message can be traced in the elements of spiritual purification (tazkiyah al-nafs). In the novel The Missing Piece, elements of tazkiyah al-nafs will be classified in terms of two relationships; the relationship of humans with Allah (habl min Allah) and the relationship of human beings with one another (habl min al-nas). Based on this concept of tazkiyah al-nafs, the female character in the novel The Missing Piece in both parts one and two, can be seen to convey a number of spiritual messages that make up aspects of female personality in Islam. This includes aspects of aqidah (creed) and ibadah (worship) in line with spiritual concepts and suggestions for the process of the purification of the soul (tazkiyah al-nafs). The potential of women authors in the field of Islamic spirituality needs to be given attention, apart from emphasizing moral issues and the quality of female characters. This can also be seen as an effort to elevate women’s writing to be on par with the men’s; it can, in fact, make women’s writing a guide for the formation of an exceptional ummah (Islamic community).